2016
DOI: 10.1007/s40119-016-0069-z
|View full text |Cite|
|
Sign up to set email alerts
|

Sodium-Glucose Cotransporter 2 (SGLT2) Inhibitors and Cardiovascular Disease: A Systematic Review

Abstract: Sodium-glucose cotransporter 2 (SGLT2) inhibitors are a novel class of drugs that have been extensively investigated for the treatment of hyperglycemia in type 2 diabetes mellitus (T2DM). These drugs reduce hyperglycemia by blocking renal glucose reabsorption, thereby promoting increased renal glucose excretion. Beyond glycemic control, these drugs have other beneficial effects on cardiovascular (CV) risk factors. The present review discusses the potential role of SGLT2 inhibitors in treating CV complications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 33 publications
0
14
0
4
Order By: Relevance
“…Sodium‐glucose cotransporter 2 inhibitors (SGLT2i), a novel class of glucose‐lowering medications for the treatment of diabetes, inhibit the transport of glucose in the kidney, decreasing glucose reabsorption and increasing glucosuria to reduce blood glucose levels . SGLT2i action is independent of insulin, and hypoglycaemia is less frequently reported compared with many other classes of antihyperglycaemic agents . Beyond glucose control, SGLT2i confer additional favourable effects on conventional cardiovascular risk factors, such as lowering blood pressure and body weight .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sodium‐glucose cotransporter 2 inhibitors (SGLT2i), a novel class of glucose‐lowering medications for the treatment of diabetes, inhibit the transport of glucose in the kidney, decreasing glucose reabsorption and increasing glucosuria to reduce blood glucose levels . SGLT2i action is independent of insulin, and hypoglycaemia is less frequently reported compared with many other classes of antihyperglycaemic agents . Beyond glucose control, SGLT2i confer additional favourable effects on conventional cardiovascular risk factors, such as lowering blood pressure and body weight .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 SGLT2i action is independent of insulin, and hypoglycaemia is less frequently reported compared with many other classes of antihyperglycaemic agents. 3 Beyond glucose control, SGLT2i confer additional favourable effects on conventional cardiovascular risk factors, such as lowering blood pressure and body weight. 4,5 Two recent major clinical trials employing SGLT2i reported an impressive beneficial effect of SGLT2i on cardiorenal outcomes.…”
mentioning
confidence: 99%
“…Emellett a ketontestek gátolják a szabad zsírsavak felvételét és oxidációját az ektópiásan lerakódott, zsírral telített szívizomban az oxidatív stressz okozta szöveti és funkcionális károsodást. 1 A fentiek értelmében a zsírsav-és glukózoxidáció helyett a több energiát (mitokondriális ATP-t) nyújtó, enyhe ketonaemia (döntően a β-hidroxi-vajsav) javíthatja a myocardi-um és a vesék keringését, anyagcseréjét, működését. 1 Experimentális állatmodellekben igazolták az empagliflozinnak az inzulinrezisztenciát és a proinflammatorikus citokinek (TNF-α, IL-6, MCP-1) mérséklő hatását.…”
Section: Az Sglt-2-gátlók Kardiovaszkuláris éS Renalis Hatásainak Elmunclassified
“…A T2DM prevalenciája 6,9-10,2% közötti a fejlett országok, közel 7% a fejlődő országok felnőtt lakosságának körében. 1 A T2DM önmagában kb. 5-10 évvel rövidíti meg a várható élettartamot, a betegek 80%-a kardiovaszkuláris betegségben hal meg.…”
unclassified
See 1 more Smart Citation